Response of Entomopathogenic Fungus Paecilomyces fumosoroseus on Drought Stress Factor - Wafa, Ali; Purnomo, Hari; Hasjim, Saifuddin; Triharyadi, Nanang (Jurnal ILMU DASAR, 2021)
The entomopathogenic fungus Paecilomyces fumosoroseus (common name: Isaria fumosorosea) can utilize to control white fly population. Bemisia tabaci or white fly has become key pest in soybean cultivation. It reported became resistance due to chemical pesticide. Some of new strain has been emerge as chemical pesticide resultant However, to develop P. fumosoroseus as biopesticide hide a problem. The environmental drought factor (temperature and water stress) become major problem. This research aimed to determine effect of environmental factor like temperature and water stress to growth and effectivity of P. fumosoroseus, due to selection an isolat were persist to drought factor. In this research has been used two different isolat of P. fumosoroseus, that is Wirowongso 1 isolat and Mumbulsari 5 isolates. This research had been conducted with five different treatments. First is a growth test under temperature stress, in vitro germination test under temperature stress and in vitro germination test under water stress, and virulence test under temperature and under water stress. The result showed that the increase a temperature and of water stress, directly make decreased of growth, germination and effectively. That effect has made different effect to growth, germination and effectivity on both isolat. The results showed that the isolat WR 1 test result showed the isolat WR 1 more persist to each drought factor. It became more valuable to develop as biopesticide among other.Keywords: Bemicia tabaci, germination, isolat, Isaria fumosorosea, in-vivo.